Effect of calcined clays from Victoria, Australia as cement substitution in ternary blended cement systems - Rackel San Nicolas; Tianchun Wang; Madhuwanthi Rupasinghe (Case Studies in Construction Materials, 2024)
Due to the high embodied carbon of cement and limited availability of conventional supplementary cementitious materials (SCMs), calcined clay has gained numerous attentions worldwide as an alternative SCM. This study explores the potential of four kaolinic clay-rich soils from waste streams in Victoria, Australia, as SCMs. The clays are compared to three commercial calcined clay products from different countries after undergoing grinding and calcination processes. The research assesses physical, chemical, and mineralogical characteristics, as well as pozzolanic activity in ternary cement systems. Results highlight the importance of fineness and calcined kaolinite content in influencing performance. Overall, the study demonstrates the feasibility of Victorian clays as SCM, even from waste streams, with suitable calcination procedures, contributing to sustainable alternatives in cement production.